Market timing and selectivity: evaluating both contributions towards the performance of portuguese equity funds - Govan, Chandni (2011)
This study attempts to understand the selectivity and market timing abilities of the Portuguese mutual fund managers. Therefore, the focus of the present investigation will be the evaluation of the performance of 51 Portuguese Equity Funds between January 2001 and December 2010. In order to achieve this, the methodology developed by Merton and Henriksson in 1981 will be used. The Jensen measure (1968) will also be applied in order to compare the results. Additionally, the problem of heteroscedasticity and autocorrelation of the errors will also be addressed, where the following methods will be used: the method of White (1980), the method of Newey-West (1987) and the method of Cochrane-Orcutt (1949). The results of this study shows that there is neither clever selectivity (security selection) nor skillful market timing abilities evidenced by most of the analyzed Equity Fund managers which is consistent with prior studies realized by Romacho (2004) and Afonso (2010). Other finding is regarding the negative correlation between the both abilities which is more evident in the international group of funds.